PERTUMBUHAN ASURANSI SYARIAH DI DUNIA DAN INDONESIA - Muhammad Maksum (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2011)
The movement of Islamic insurance growth as one of an Islamic finance instruments is not as fast as the growth of Islamic  banking. Nevertheless, it shows a significance growth wether in the world or Indonesia. In the debate over the legal status of insurance, the insurance based on mutual help and free of ribâ can be an alternative for those who want a lawful economic  transactions. The increasing public appreaciation of the Islamiceconomic system allows the growth of Islamic insurance in the future rapidlyDOI: 10.15408/aiq.v3i1.2495